Implementation of Perceived Organizational Support (POS) to Support Employee Performance: A Case Study of the Yogyakarta Regional Personnel Agency - Musdalifah Musdalifah; St. Nurhikma Maulida; Diah Astrini Amir (Universitas Teuku Umar, 2022)
The purpose of this study was to analyze and elaborate on the role of Perceived Organizational Support (POS) in supporting the performance of employees at the Regional Personnel Agency (BKD), Special Region of Yogyakarta. POS is an employee's perception of how the organization contributes and cares about their well-being. In this study, researchers identified a number of factors thought to play a role in employee perceptions of the organization, namely organizational justice (four model justice), supervisor support, organizational rewards, and job conditions. This research is descriptive qualitative with data collection techniques carried out by conducting structured and in-depth interviews with key informants. The results showed that employees perceive the organization to treat them fairly (in terms of procedural, interpersonal, informational, and distributive). Employees also perceive getting good support from supervisors, the organization has implemented a good reward system (intrinsic and extrinsic) and conducive working conditions. In line with that, the results of this study indicate that BKD employees perceive the organization as contributing to and caring about their well-being